1941
DOI: 10.1111/j.1151-2916.1941.tb14833.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray Study of Lime‐phosphate and Lime‐borate Glass*

Abstract: X-ray diffraction patterns have been made of two lime-phosphate glasses with compositions of 23% and 28% of CaO by weight, and of one lime-borate glass with 25% o f CaO. Fourier analyses of these patterns were carried out, and the radial distribution curves were plotted. In the lime-phosphate glasses, each phosphorus is tetrahedrally bonded to 4 oxygens at a distance of 1.57 A, and each oxygen is bonded to either 1 or 2 phosphorus atoms. The calcium ions, Ca++, are situated in the holes in the phosphorusoxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1958
1958
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 2 publications
0
14
0
2
Order By: Relevance
“…This method has been applied to several soda-silicate glasses [4], to potash silicate glasses [5], and to some soda silicate glasses containing lime [6]. Such work has been done, also, on some simple borate glasses [7], and phosphate glasses [8].…”
Section: Differential Diffraction Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been applied to several soda-silicate glasses [4], to potash silicate glasses [5], and to some soda silicate glasses containing lime [6]. Such work has been done, also, on some simple borate glasses [7], and phosphate glasses [8].…”
Section: Differential Diffraction Patternsmentioning
confidence: 99%
“…Compu ted possi bilities X·ray e ,·id ence R em" rk s and estima tes of E s tim ated shielding (8) pea ks lJartJief '1'ilton [5] (W arren)…”
Section: T a Ble 3 Radial Distl·ibution Oj Ions M·ound Potassiu M I mentioning
confidence: 99%
“…In all spectra, the peak with the chemical shifts of around 3 ppm was confirmed and the shapes of the spectra at a constant CaO/SiO 2 ratio were in accordance with each other within the limits of experimental error. According to Grussaute et al [13], this chemical shift of 3 ppm is that of the monophosphate complex ion PO 4 3− in the CaO-SiO 2 -PO 2.5 system.…”
Section: Methodsmentioning
confidence: 96%
“…They confirmed that the distribution ratio was constant up to 2 mass% of phosphorus in the slag and that it increased linearly beyond 2 mass%. To explain this phosphate-concentration dependence of the distribution ratio, they presumed that Reaction (1) took place and that the predominant species of phosphorus in the slag was the monophosphate complex ion PO 4 3− , up to 2 mass% of the phosphorus in the slag. At higher phosphorus concentrations, Reaction (2) occurred and the diphosphate complex ion P 2 O 7 4− was the dominant species in the slag phase.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation